2010
DOI: 10.1111/j.1758-2229.2009.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental occurrence and clinical impact of Vibrio vulnificus and Vibrio parahaemolyticus: a European perspective

Abstract: Vibrio vulnificus and Vibrio parahaemolyticus are ubiquitous Gram-negative bacterial pathogens found naturally in marine and estuarine waters, and are a leading cause of seafood-associated bacterial illness. These pathogens are commonly reported in the USA and in many Asian countries, including China, Japan and Taiwan; however, there is growing concern that V. vulnificus and V. parahaemolyticus may represent an important and increasing clinical problem in Europe. Several factors underlie the need for a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
200
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(210 citation statements)
references
References 86 publications
6
200
1
3
Order By: Relevance
“…The test statistic D 2 describes the overall model performance and is given in the upper left corner of each sub-plot trh gene, but not for tdh. Comparisons with other studies show that generally between 3 and 5 % of environmental V. parahaemolyticus isolates bear either of the two virulence gene markers [67,68]. This suggests that the ratio observed here is realistic, although more strains need to be checked for more reliable evidence.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The test statistic D 2 describes the overall model performance and is given in the upper left corner of each sub-plot trh gene, but not for tdh. Comparisons with other studies show that generally between 3 and 5 % of environmental V. parahaemolyticus isolates bear either of the two virulence gene markers [67,68]. This suggests that the ratio observed here is realistic, although more strains need to be checked for more reliable evidence.…”
Section: Discussionsupporting
confidence: 58%
“…Presence of the trh gene alone seems to be a common characteristic of V. parahaemolyticus communities in Northern European waters and has been shown for several studies in this region [39,69,70]. Up to now, only tdh-positive strains were associated with V. parahaemolyticus infections in Europe, however [68], and tdh is the gene that has been mainly attributed to haemolysis [71]. Despite this, two strains that were identified as being tdhand trh-negative exhibited haemolytic capacity in the Kanagawa test.…”
Section: Discussionmentioning
confidence: 84%
“…The displacement of the density fronts towards the interior of the rias during downwelling periods may represent an important supply of oceanic zooplankton and a parallel source of V. parahaemolyticus populations attached to the zooplankton. Coincidentally, one of the largest V. parahaemolyticus outbreaks detected in Europe occurred in Galicia in 1999(Lozano-Leon et al, 2003 and was concurrent with the incursion in the rias of warm tropical waters and the presence of large patches of zooplankton (Baker-Austin et al, 2010). Similar oceanographic conditions have been observed to be related to large outbreaks of V. parahaemolyticus in Peru (Martinez-Urtaza et al, V. parahaemolyticus counts were observed in the present study to increase in parallel to increased zooplankton density, measured as the number of individuals per cubic metre of water.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has related major epidemic outbreaks of V. parahaemolyticus to the incursion of oceanic waters of subtropical origin in coastal areas. The emergence and spread of infections in Peru, Spain, Chile and Alaska occurred concurrently with the arrival and movement of warm oceanic waters along the coast (MartinezUrtaza et al, 2008a(MartinezUrtaza et al, , 2010Ansede-Bermejo et al, 2010;Baker-Austin et al, 2010), and with an increase in the occurrence of atypical warm-water zooplankton (Baker-Austin et al, 2010;MartinezUrtaza et al, 2010). The existence of a mechanism for the oceanic migration of V. parahaemolyticus populations implies that V. parahaemolyticus can persist in the open sea long enough to allow transport across the oceans under adverse ecological conditions for the presence of these bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies reported that the number of Vibrio infections correspond closely with the sea surface temperature pointing to a possible link to climate change related phenomena (e.g. global warming, heat waves) (Baker-Austin et al, 2010. Böer et al (2013) reported that Vibrio alginolyticus, V. parahaemolyticus, V. vulnificus and V. cholerae occurred in water and sediments in the central Wadden Sea and in the estuaries of the rivers Ems and Weser.…”
Section: Introductionmentioning
confidence: 99%